2015
DOI: 10.1002/dneu.22362
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin‐dependent plasticity of neurotransmitter segregation in the rat superior cervical ganglion in vivo

Abstract: Neurons are able to segregate transmitters to different axon endings. Segregation is a plastic neuronal feature; it can be modulated by synaptic environment. We have demonstrated that neurotrophin and other cellular factors regulate segregation in sympathetic neurons in culture. Herein we tested the hypothesis that sympathetic neurons in vivo are also capable to exhibit neurotrophin-dependent plasticity of segregation. To explore the effect of neurotrophin on segregation, we reduced ganglionic NGF content by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Thus, addition of ciliary neurotrophic factor (CNTF) increases the degree of segregation of NE and NPY in varicosities of sympathetic ganglionic neurons co-cultured with cardiomyocytes (Vega et al, 2010 ). Furthermore, the neurotrophin, nerve growth factor (NGF) changes the segregation of ACh and methionine-enkephalin (mENK) in preganglionic sympathetic neuronal varicosities in vivo (Vega et al, 2016 ). Considering these evidences, we explored whether plastic changes in the segregation of neurotransmitters can also occur in physio-pathologic conditions, like stress and hypertension, conditions that course with augmented sympathetic activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, addition of ciliary neurotrophic factor (CNTF) increases the degree of segregation of NE and NPY in varicosities of sympathetic ganglionic neurons co-cultured with cardiomyocytes (Vega et al, 2010 ). Furthermore, the neurotrophin, nerve growth factor (NGF) changes the segregation of ACh and methionine-enkephalin (mENK) in preganglionic sympathetic neuronal varicosities in vivo (Vega et al, 2016 ). Considering these evidences, we explored whether plastic changes in the segregation of neurotransmitters can also occur in physio-pathologic conditions, like stress and hypertension, conditions that course with augmented sympathetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, later evidence showed that neurons are able to segregate their neurotransmitters, and independently store and release them at distinct terminals, allowing neurons to exert each transmitter function separately (Fisher et al, 1988 ; Hattori et al, 1991 ; Morales et al, 1995 ; Sámano et al, 2012 ; Zhang et al, 2015 ). Like other neurons, sympathetic ones have this capability to segregate their neurotransmitters (Morales et al, 1995 ; Chanthaphavong et al, 2003 ; Sámano et al, 2006 , 2009 ; Vega et al, 2010 , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gärtner and Staiger (2002) demonstrated that short high-frequency bursts of stimuli that induce LTP also evoke the instantaneous secretion of BDNF in primary cultures of hippocampal neurons. The fact that BDNF and NGF are expressed in the neurons of the SCG in adult rats (Wetmore and Olson, 1995; Vega et al, 2016) supports this possibility.…”
Section: Discussionmentioning
confidence: 96%
“…Segregation between ACh and m-Enk can be modified by endogenous neurotrophic factors in the SPN in vivo. We showed that axotomy produces a decrease in endogenous nerve growth factor (NGF) content and an enhancement of ACh and m-Enk segregation in the rat SCG; these effects were counteracted by NGF administration ( Vega et al, 2016 ; Figure 1 ). Considering these findings, we wondered whether neurotransmitter segregation varies in different physiopathological conditions, such as stress and hypertension.…”
Section: Neurotransmitter Segregation Plasticitymentioning
confidence: 99%